2012
DOI: 10.1021/je300086w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physical Properties of Choline Carboxylate Ionic Liquids

Abstract: A series of choline carboxylate ionic liquids (ILs) have been synthesized by neutralization of choline hydroxide solution with acetic, propanoic, butanoic, pivalic, and hexanoic acids. The salts so obtained were characterized by NMR spectroscopy, thermal methods, and elemental analysis. Key physical properties (density, viscosity, and refractive index) were measured for the propanoate, butanoate, and hexanoate salts at temperatures from (293.15 to 353.15) K. The densities were used to estimate the molecular vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 34 publications
6
85
2
Order By: Relevance
“…This is in contrast to the results of Petkovic et al [7] (where cytotoxic effects follow as be explained according to the stated in T-SAR concept [40,42]. Also the results are not in line with those of Muhammad et al, who reported that cytotoxicity of ChC m with m = 2, 3, 4, 6 on the human breast cancer cell line MCF-7 decreases with increasing chain length [8]. This study agrees partly with the results found by Petkovic et al [7] where the cytotoxicity increases with increasing chain length (see m = 2–4 and 6–10) and partly with the one of Muhammad et al [8], where the cytotoxicity decreases with increasing chain length (see m = 4–6).…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…This is in contrast to the results of Petkovic et al [7] (where cytotoxic effects follow as be explained according to the stated in T-SAR concept [40,42]. Also the results are not in line with those of Muhammad et al, who reported that cytotoxicity of ChC m with m = 2, 3, 4, 6 on the human breast cancer cell line MCF-7 decreases with increasing chain length [8]. This study agrees partly with the results found by Petkovic et al [7] where the cytotoxicity increases with increasing chain length (see m = 2–4 and 6–10) and partly with the one of Muhammad et al [8], where the cytotoxicity decreases with increasing chain length (see m = 4–6).…”
Section: Resultscontrasting
confidence: 74%
“…Choline carboxylates were found to exert only minor toxic activity on these organisms. Also Muhammad et al found just slight cytotoxic effects on the human breast cancer cell line MCF-7 for choline carboxylates ChC m with m = 2,3,4, 6 [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The COSMO-RS model has been successfully used in the past to estimate the thermodynamic properties of systems containing ionic liquids, including liquid-liquid equilibrium and activity coefficients of its mixture with water or organic solutes [52][53][54][55][56][57][58][59]. After evaluating the capacity of the COSMO-RS model to describe the experimental activity coefficients, this is used to analyze and discuss the molecular interactions that affect the mixing properties of the cholinium-ionic liquids and water, which are also supported by ab initio calculations [60][61][62][63] [15,64]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was calibrated with Millipore-grade water using ILs with data previously established by our research group [12][13][14]. The viscosities and densities of the ILs were measured in the temperature range of 293.15-373.15 K with ±0.01 K accuracy and uncertainties of 0.5 % and ±5 9 10 -4 gÁcm -3 , respectively.…”
Section: Viscosity and Densitymentioning
confidence: 99%
“…The standard entropies calculated within the range of 283.7-409.6 JÁmol -1 ÁK -1 are presented in Table 6 [13,24,27]. The lattice energy of a salt is associated with the potency of interactions of its ions and predicts their relative stabilities.…”
Section: Estimation Of Volumetric Propertiesmentioning
confidence: 99%